Vaccination of pregnant women - Adamczyk-Gruszka, Olga (Journal of Education, Health and Sport, 2021)
Vaccination of pregnant women for their protection and the protection of the fetus and the child is not common. Health professionals’ prejudices about immunization of pregnant women increase the concerns of women and their families. Such behavior is not supported by scientific data. The literature describes the harmlessness of the vaccine for mother and child in the case of seasonal, pandemic or meningococcal flu, pneumococcus, tetanus, acellular pertussis, human papillomavirus, cholera, hepatitis A, Japanese encephalitis, rabies, anthrax, smallpox, yellow fever, mumps, measles and rubella, typhoid fever, inactivated or attenuated polio vaccines, and Bacillus Calmétte Guerin vaccines. Many scientific studies show the beneficial effects of the flu vaccine for mother and baby and the pertussis vaccine for the baby. Staff of Obstetrics and Gynecology Departments, family doctors and midwives should include vaccinations in their standard clinical care. Strategies are needed that are effective in reducing parents’ reluctance to vaccinate. Every pregnant woman should be aware that the lack of vaccines before pregnancy does not preclude the use of some of them during pregnancy.